2021
DOI: 10.1021/acs.accounts.1c00050
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Selectivity Control in Ni- and Pd-Catalyzed Cross-Couplings Involving Carbon–Oxygen Bond Activation

Abstract: Conspectus Transition-metal-catalyzed C–O bond activation provides a useful strategy for utilizing alcohol- and phenol-derived electrophiles in cross-coupling reactions, which has become a research field of active and growing interest in organic chemistry. The synergy between computation and experiment elucidated the mechanistic model and controlling factors of selectivities in these transformations, leading to advances in innovative C–O bond activation and functionalization methods. Toward the rational design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 75 publications
1
33
0
Order By: Relevance
“…Subsequent C(acyl)-O oxidative addition of 2-pyridyl ester to Ni I prefers to occur through a five-membered cyclic transition state TS-2 (DG °= 15.5 kcal mol À1 ). [18] The chelation of 2-pyridyl group with the metal center observed in TS-2…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent C(acyl)-O oxidative addition of 2-pyridyl ester to Ni I prefers to occur through a five-membered cyclic transition state TS-2 (DG °= 15.5 kcal mol À1 ). [18] The chelation of 2-pyridyl group with the metal center observed in TS-2…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, nickel is also known to effectively cleave C–O bonds. 3 In most cases, such reactions take place with C(sp 2 )–O bonds including aryl, 3,8 vinyl, 9 and acyl 10 C–O bonds. An important aspect of C(sp 2 )–O activation is the use of Lewis acidic boron, zinc or magnesium to help overcome the high-barrier of the oxidative addition of a C–O bond.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of C(sp 2 )–O activation is the use of Lewis acidic boron, zinc or magnesium to help overcome the high-barrier of the oxidative addition of a C–O bond. 3,8–10 The Martin group has proposed that the Lewis acidity of the Grignard reagent is critical in the Ni-catalyzed Kumada–Corriu reaction of cyclic vinyl ethers. 9 b While the Agapie group has shown that Ni(0) reacts with an aryl ether to give a Ni( ii ) aryl alkoxide species, as the C–O oxidative addition product, 4 d , e similar studies for Ni(0) mediated C–O bond activation of vinyl ethers are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, multiple C–H activation reactions make use of cheap compounds, while alleviating the need for laborious synthetic manipulation. To efficiently produce high value-added chemicals in a minimum of operations, it should be one of the ultimate goals for new methodology development . To this end, direct functionalization of ArCO 2 H is of particular interest with controllable site specificity for diversification of the parent aromatic nucleus by π-extension .…”
mentioning
confidence: 99%